Graduation Modalities and Educational Trends in the Psychology Program (Docentes 2.0 Journal, 2026)
The completion of university studies represents a significant milestone in professional training, as reflected in graduation modalities that certify the acquisition of specialized skills and knowledge. The objective of this research was to analyze the graduation modalities preferred by Psychology students at private universities in La Paz, Bolivia, given the need to understand the trends in the selection of options such as theses, degree projects, or comprehensive exams, in a context where these decisions impact the quality of education and scientific production. A quantitative approach was employed within a positivist paradigm, using a deductive method and a non-experimental, descriptive, and longitudinal design. The research analyzed secondary data from 614 thesis defenses conducted between 2021 and 2024. The sample included valid records from nine private universities. Document analysis and a structured spreadsheet were used as instruments, and the data were processed with descriptive statistics in SPSS. The results revealed that the Comprehensive Exam was the most frequent modality (42.1%), followed by the Thesis (34.7%) and the Degree Project (15.5%). The least common modalities were Academic Excellence (5.4%) and Directed Work (2.3%). Institutional differences and sustained growth in research-based options were observed. It was concluded that, although practical modalities predominate, a significant commitment to research persists. The findings provide guidance for academic policies, reinforce methodological support, and promote scientific production through graduation requirements, contributing to the strengthening of professional training in psychology in the Bolivian context.
Keywords: Educational research; thesis defenses; graduation modalities; psychology; private universities